Mitigasi Karbon Melalui Pemanfaatan Sampah Plastik Menjadi Paving Blok Plastik: Pendekatan Ekonomi Sirkular untuk Pembangunan Berkelanjutan - Laksana, Rifo Nur Laksana Restu; Rahmat Rahmat; Dean Anggara Putra; Jefri Imron; Marhaendra Natawibawa; Hery Sumardiyanto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Global climate change driven by greenhouse gas (GHG) emissions, particularly carbon dioxide (CO₂), has become the greatest challenge of this century. At the same time, the accumulation of plastic waste has emerged as a massive environmental crisis. This paper examines the potential utilization of plastic waste into paving blocks as a carbon mitigation strategy and a waste management solution. This approach not only reduces the volume of plastic waste in the environment but also has the potential to lower the carbon footprint of conventional construction material production and contribute to the circular economy. The analysis involves a comparison of the carbon footprint between plastic-based and conventional paving blocks, as well as an estimation of the carbon mitigation potential at various scales of implementation. The findings indicate that material substitution and the incorporation of plastic into durable products offer significant contributions to emission reduction and foster sustainable development.